Remote ischemic postconditioning increased cerebral blood flow and oxygenation assessed by magnetic resonance imaging in newborn piglets after hypoxia-ischemia - Kerrn-Jespersen, Sigrid; Andersen, Mads; Bennedsgaard, Kristine; Andelius, Ted Carl Kejlberg; Pedersen, Michael; Kyng, Kasper Jacobsen; Henriksen, Tine Brink (Frontiers in Pediatrics, 2022)
Background We have previously investigated neurological outcomes following remote ischemic postconditioning (RIPC) in a newborn piglet model of hypoxic-ischemic encephalopathy. The aim of this study was to further investigate potential mechanisms of neuroprotection by comparing newborn piglets subjected to global hypoxia-ischemia (HI) treated with and without RIPC with regards to measures of cerebral blood flow and oxygenation assessed by functional magnetic resonance imaging. Methods A total of 50 piglets were subjected to 45-minutes global HI and randomized to either no treatment or RIPC treatment. Magnetic resonance imaging was performed 72 hours after the HI insult with perfusion-weighted (arterial spin labelling, ASL) and oxygenation-weighted (blood-oxygen-level-dependent, BOLD) sequences in the whole brain, basal ganglia, thalamus, and cortex. Four sham animals received anesthesia and mechanical ventilation only. Results Piglets treated with RIPC had higher measures of cerebral blood flow in all regions of interest and the whole brain (mean difference: 2.6 ml/100g/min, 95% CI: 0.1;5.2) compared with the untreated controls. They also had higher BOLD values in the basal ganglia and the whole brain (mean difference: 4.2 T2*, 95% CI: 0.4;7.9). Measures were similar between piglets treated with RIPC and sham animals. Conclusion Piglets treated with RIPC had higher measures of cerebral blood flow and oxygenation assessed by magnetic resonance imaging in the whole brain and several regions of interest compared with untreated controls 72 hours after the HI insult. Whether this reflects a potential neuroprotective mechanism of RIPC requires further study.